Estimación y comparación de variables biométricas de la especie Lepidocaryum tenue “irapay” en área natural y plantación, Loreto, Perú, 2021 - Vasquez Amasifuen, Cesar Paul (2022)
Lepidocaryum tenue "irapay" is a non-timber forest species of high socioeconomic value. Previous research reports the biometric variables of this species in its natural habitat. However, they are unknown in plantations because they have not yet been studied. The objective of this research was to estimate and compare the biometric variables of a Lepidocaryum tenue population in its natural habitat and in plantation. The biometric variables of this species were obtained through a census of a plot within a natural stand and in a plantation in northwestern Amazonia. The research design was quantitative, cross-sectional and comparative; descriptive and inferential statistics were used; the Wilcoxon nonparametric test was used to verify the existence of significant statistical differences between the means of the biometric variables of both populations. 751 palms were recorded in the natural area, and 334 in plantation. The mean total height of both populations did not show significant differences (p > 0.05), while the mean stem height, stem diameter, number of leaves per palm, number of fruits per palm in natural area and in plantation showed significant differences (p < 0.05). The 0.39 % of palms in natural area and 13.77 % of palms in plantation had flowers. The juvenile class in both populations contributed with the highest number of palms. These findings suggest that the environment where Lepidocaryum tenue grows influences its biometric variables and highlight the need to study the physical, chemical and biological factors that trigger these differences.